Efektivitas Evaluasi Pembelajaran Pendidikan Agama Islam Di SD Kosambi Negeri Kosambi - Komalasari Komalasari; Tubagus Maruf Ansori; Siska Siska; Saefudin Zuhri; Wahyu Hidayat (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The research carried out aims to determine the effectiveness of evaluating Islamic Religious Education learning at Kosambi State Elementary School. This research uses a qualitative approach method, in the type of field research (field research). From the results of this research, it can be concluded that the effectiveness of PAI learning evaluation at Kosambi State Elementary School shows that teachers are successful in measuring student achievement through various comprehensive evaluation methods, despite facing challenges such as students' lack of interest in learning and concentration. Solutions in the form of interactive learning, use of technology, and rubric-based evaluation help increase student focus, understanding, and involvement, thereby supporting teachers' efforts to create optimal and meaningful learning.